Students' management of goals in the natural classroom setting: Methodological implications - Marina Serra de Lemos (2004)
The conceptualization of goals as projects of person-environment relationships emphasizes the mutual influences of individuals and situations. This interactionistic view leads to a focus goal research on current behaviour in proximal contexts. Moreover, within the real classroom context, as students encounter situations implying new demands and new opportunities, diverse and multiple goals are potentially elicited. Exploring these assumptions, the present study examined the strategies that students use to deal with multiple goals during ongoing classroom activities. Instead of valuing behavioural and phenomenological approaches as alternative models, we used both observed behaviour and reported intentions viewed as representing two different levels of action, to allow a more comprehensive understanding of students' strategies. This approach is consistent with a contextualized view of action orientation, and with a view of goal-directed behaviour as hierarchically organized (Frese & Stewart, 1984, Silbereisen Eyferth, 1986; Volpert, 1982). To this effect, in a multiple case study of eight (6th-grade) students, methods included (a) videotaping, and interpretation of the student's actual behaviour (the researcher perspective) in natural classroom settings, and (b) semi-structured interviews regarding the student's individual purposes (subjective perspective)for those activities. Results revealed diverse forms of goal management such as the automatization of certain action-orientations and the monitoring of action emergence and duration. Moreover, results illuminated the function of certain goals within the overall action sequence.